2018
DOI: 10.1093/bioinformatics/bty024
|View full text |Cite
|
Sign up to set email alerts
|

Optimal water networks in protein cavities with GAsol and 3D-RISM

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 7 publications
(7 reference statements)
2
27
0
Order By: Relevance
“…17 In a number of publications it was shown that this physically rigorous computational approach reproduced with high accuracy experimental data on the structure of solvation shells for various systems. [18][19][20] For PEX14 structures, we revealed an excellent agreement between the predicted water positions and high-resolution X-ray data (PDB ID = 5L87; res. = 0.87 Å, see Fig.…”
supporting
confidence: 52%
“…17 In a number of publications it was shown that this physically rigorous computational approach reproduced with high accuracy experimental data on the structure of solvation shells for various systems. [18][19][20] For PEX14 structures, we revealed an excellent agreement between the predicted water positions and high-resolution X-ray data (PDB ID = 5L87; res. = 0.87 Å, see Fig.…”
supporting
confidence: 52%
“…15) was used to achieve convergence for hydration-site occupancy and thermodynamics predictions for solvent-exposed and occluded binding sites 20 . Using 3D-RISM site-distribution function [49][50][51] and GAsol 42 for initial placement of water molecules, WATsite then performs explicit water MD simulations of each protein. Finally, explicit water occupancy and free energy profiles of each hydration site (i.e., high wateroccupancy spot) in the binding site are computed.…”
Section: Methodsmentioning
confidence: 99%
“…10). Both of our methods were compared to WATsite 18 and GAsol (3D-RISM) 42 . It should be noted that WATsite had been previously tested to reproduce Xray water molecules 18,20,27 .…”
Section: Neural Network For Semantic Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The taxanes set contains a series of complex natural product derivatives (macrocycles) but that has led to very successful COMBINE models in the past [19,20]. The BRD4-BD1 set is made of a congeneric series of pyridinone derivatives designed to interact with the complex combination of flexible residues and the "dry" water molecules network in the binding site of the bromodomain that recognizes an acetyl-lysine residue [36]. These two binding sites have very different properties in terms of electrostatics and shape and were chosen to obtain a general overview of the performance of AL-COMBINE models beyond the HIV-PR set.…”
Section: Overall Performance Of Active Learningmentioning
confidence: 99%